(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The rapid development of industrial production and scientific research requires high accuracy and reliability of geometric measurements. Establishing a calibration laboratory for modern geometric measuring instruments is crucial to ensure measurement traceability, compliance with international standards, and enhancement of product quality. This article explores the scientific and methodological foundations for organizing such laboratories, focusing on standardization, metrological assurance, quality management, and the integration of advanced technologies.